A compound Kinoform/Fresnel zone plate lens with 15 nm resolution and high efficiency in soft x-ray. (7th March 2023) - Tong, Xujie; Chen, Yifang; Mu, Chengyang; Chen, Qiucheng; Zhang, Xiangzhi; Zeng, Guang; Li, Yuchun; Xu, Zijian; Zhao, Jun; Zhen, Xiangjun; Mao, Chengwen; Lu, Hongliang; et al.
Abstract: X-ray microscope as an important nanoprobing tool plays a prevailing role in nano-inspections of materials. Despite the fast advances of high resolution focusing/imaging reported, the efficiency of existing high-resolution zone plates is mostly around 5% in soft x-ray and rapidly goes down to 1%–2% when the resolution approaches 10 nm. It is well known that the rectangular zone shape, beamstop, limited height/width ratios, material absorption of light and structural defects are likely responsible for the limited efficiency. Although zone plates with Kinoform profile are supposed to be efficient, progress for achieving both high resolution (<30 nm) and high efficiency (>5%) have hardly been addressed in soft x-ray. In this work, we propose a compound Kinoform/Fresnel zone plate (CKZP) by combing a dielectric Kinoform zone plate with a 15 nm resolution zone plate. Greyscale electron beam lithography was applied to form the 3D Kinoform zone plate and atomic layer deposition was carried out to form the binary zone plate. Optical characterizations demonstrated 15 nm resolution focusing/imaging with over 7.8% efficiency in soft x-ray. The origin of the efficiency improvement behind the proposed compound lens is theoretically analyzed and discussed.